Metaphorical Expressions in Coldplay’s ‘Fix You’: A Cognitive Semantic Perspective - Agustin, Elyzabeth; Musyarofah, Lailatul; Aisyah, Siti (Journal of English Teaching, Literature, and Applied Linguistics, 2025)
Introduction: Language serves as a symbolic system for organizing thought, where metaphors act as vital cognitive tools rather than mere decorative devices. Gap: There is a lack of systematic exploration regarding how inner experiences in popular lyrics utilize universal cognitive patterns through Conceptual Metaphor Theory (CMT). Purpose: This study aims to identify and classify metaphorical expressions in Coldplay’s "Fix You" to demonstrate how concrete images explain abstract emotions. Method: A descriptive qualitative method was used to analyze eight identified metaphorical expressions, categorized based on Lakoff and Johnson’s framework. Main Findings: The analysis reveals that abstract emotional states are systematically mapped onto physical source domains, such as Journey, Damage, and Possession. Orientational metaphors emerged as the most dominant type, indicating a reliance on spatial direction to communicate recovery. Conclusion: The lyrics utilize universal cognitive schemas to convey resilience, confirming that popular songs are rich cognitive artifacts for linguistic analysis. Limitation: This research is limited to a single lyrical analysis and does not include empirical data from listeners’ perspectives.